Genotyping Method and Frequency of ADRB3-rs4994 Single Nucleotide Polymorphism Genotypes in Hanoi 3-5 Years Old Chidren - Le Thi Tuyet; Nguye Thi Trung Thu; Nguyen Thi Hong Hanh; Do Thi Nhu Trang; Nguyen Thi Ngoc Lien; Tran Quang Binh; Do Nam Khanh (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2019)
The Trp64Arg (rs4994) polymorphism in codon 64 of ADRB3 (beta3-adrenergic receptor) gene is involved in the regulation of energy metabolism. This study optimizes the genotyping method of ADRB3 rs4994 polymorphism and determines the allele and genotype frequencies of this polymorphism in 3-5 years old children in Hanoi. A cross-sectional study was conducted on 100 three-to-five-year-old Hanoi children, using DNA extraction method from cheek mucosa cells. The genotyping of this polymorphism was performed by polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) method. The study optimized the method of genotyping of ADRB3 rs4994 polymorphism with Mval enzyme. In 3-5 years old children in Hanoi, T/T genotype accounted for the highest proportion (78%), C/C genotype accounted for the lowest proportion (3%). T and C allele frequencies were 0.785 and 0.125, ​​respectively. The genotypes observed were in agreement with those expected under Hardy-Weinberg equilibrium. It is necessary to apply the genotyping method and genetic distribution for genotyping the ADRB3 rs4994 polymorphism in large-scale studies in Vietnam. Keywords ADRB3, rs4994, genotyping, RFLP. References [1] T. Rankinen, A. Zuberi, Y.C. Chagnon, S.J. Weisnagel, G. Argyropoulos, B. Walts and C. Bouchard, The human obesity gene map: the 2005 update, Obesity. 14 (2006) 529-644. https://doi.org/10.1038/oby.2006.71. [2] S. Krief, F. Lönnqvist, S. Raimbault, B. Baude, A. Van Spronsen and P. Arner, Tissue distribution of β3-adrenergic receptor mRNA in man, J Clin Invest. 91 (1993) 344-349. Doi: 10.2337/db18- https://doi.org/10.2337/db18- 0462.[3] F.Lönnqvist, S. Krief, A.D. Strsberg, S. Nyberg, L.J. Emorine and P. Amer, A pathogenic role of visceral fat β3-adrenoceptors in obesity, J Clin Invest. 95 (1995) 1109-1116. Doi: https://doi.org/10.1172/JCI117758.[4] J. Walston, K. Silver, C. Bogardus, W.C. Knowler, F.S. Celi and S. Austin, Time of onset of non-insulin-dependent diabetes mellitus and genetic variation in the β3-adrenergic-receptor-gene, N Engl J Med. 333 (1995) 343-347. [5] P. Katzmarzyk, L. Perusse and C. Bouchard, Genetics of abdominal visceral fat levels, Am J Hum Biol. 11 (1999) 225-235. DOI: https://doi.org/10.1002/(SICI)1520-6300(1999)11:23.0.CO;2-J. [6] J.A. Ryuk, X. Zhang, B.S. Ko, J.W. Daily and S. Park, Association of β3-adrenergic receptor rs4994 polymorphisms with the risk of type 2 diabetes: a systematic review and meta-analysis, Diabetes research and clinical practice. 129 (2017) 86-96. https://doi.org/10.1016/j.diabres.2017.03.034.[7] N. Kurokawa, E.H. Young, Y. Oka, H. Satoh, N.J. Wareham, M.S. Sandhu and R.J. Loos, The ADRB3 Trp64Arg variant and BMI: a meta-analysis of 44,833 individuals, International journal of obesity. 32 (2008) 1240-1249. https://doi.org/10.1038/ijo.2008.90.[8] M. Daghestani, M. Daghestani, M. Daghistani, A. Eldali, Z.K. Hassan, M.H. Elamin and A. Warsy, ADRB3 polymorphism rs4994 (Trp64Arg) associates significantly with bodyweight elevation and dyslipidaemias in Saudis but not rs1801253 (Arg389Gly) polymorphism in ARDB1, Lipids in health and disease. 17 (2018) 58-66. https://doi.org/10.1186/s12944-018-0679-7[9] J. Walston, K. Silver, C. Bogardus, W.C. Knowler, F.S. Celi, S. Austin, Time of onset of non-insulin-dependent diabetes mellitus and genetic variation in the beta 3-adrenergic-receptor gene, N Engl J Med. 333 (1995) 343-347. https://doi.org/10.1056/NEJM199508103330603[10] K. Clement, C. Vaisse, B.S. Manning, A. Basdevant, B. Guy-Granda and J. Ruiz, Genetic variation in the beta 3-adrenergic receptor and an increased capacity to gain weight in patients with morbid obesity, N Engl J Med. 333 (1995) 352-354. https://doi.org/10.1056/NEJM199508103330605[11] H. Kim-Motoyama, K. Yasuda, T. Yamaguchi, N. Yamada, T. Katakura and A.R. Shuldiner, A mutation of the β3-adrenergic receptor is associated with visceral obesity but decreased serum triglyceride, Diabetologia. 40 (1997) 469-472. [12] S.G. Malik, M.R. Saraswati, K. Suastika, H. Trimarsanto, S. Oktavianthi and H. Sudoyo, Association of beta3-adrenergic receptor (ADRB3) Trp64Arg gene polymorphism with obesity and metabolic syndrome in the Balinese: a pilot study, BMC research notes 4 (2011) 167-173. https://doi.org/10.1186/1756-0500-4-167[13] E. Widen, M. Lehto, T. Kanninen, J. Walston, A.R. Shuldiner, L.C. Groop, Association of a polymorphism in the beta 3-adrenergic-receptor gene with features of the insulin resistance syndrome in Finns, N Engl J Med 333 (1995) 348-351. https://doi.org/10.1056/NEJM199508103330604[14] A.J. Biery, S.O.E. Ebbesson, A.R. Shuldiner, B.B. Boyer, The β 3-adrenergic receptor TRP64ARG polymorphism and obesity in Alaskan Eskimos, International journal of obesity. 21 (1997) 1176-1179.[15] X. Yuan, K. Yamada, K.I. Koyama, F. Ichikawa, S. Ishiyama, A. Koyanagi and K. Nonaka, β3-adrenergic receptor gene polymorphism is not a major genetic determinant of obesity and diabetes in Japanese general population, Diabetes research and clinical practice, 37 (1997) 1-7. https://doi.org/10.1016/S0168-8227(97)00064-8[16] N. Sakane, T. Yoshida, T. Umekawa, A. Kogure, Y. Takakura and M. Kondo, Effects of Trp64Arg mutation in the β3-adrenergic receptor gene on weight loss, body fat distribution, glycemic control, and insulin resistance in obese type 2 diabetic patients, Diabetes care 20 (1997) 1887-1890. https://doi.org/10.2337/diacare.20.12.1887[17] R. Bracale, F. Pasanisi, G. Labruna, C. Finelli, C. Nardelli, P. Buono and G. Oriani, Metabolic syndrome and ADRB3 gene polymorphism in severely obese patients from South Italy, European journal of clinical nutrition. 61 (2007) 1213-1219. https://doi.org/10.1038/sj.ejcn.1602640[18] G.T. Marth, E. Czabarka, J. Murvai, S.T. Sherry, The Allele Frequency Spectrum in Genome-Wide Human Variation Data Reveals Signals of Differential Demographic History in Three Large World Populations, Genetics. 166 (2004) 351-372. [19] National Center for Biotechnology Information. http://hapmap. ncbi.nlm.nih.gov/projects/SNP/snp_ref.cgi?do_not_redirect&rs=rs4994 (accessed 6 March 2019).[20] L.T. Tuyet, B.T.N. Anh, T.Q. Binh, Application of restriction fragment length polymorphirm method for genotyping BDNF rs6265 polymorphism. Journal of science of HNUE, Chemical and Biological Science, 59 (2014) 123-130. https://doi.org/10.15625/0866-7160/v37n1se.6095[21] L.T. Tuyết, T.Q. Bình, Bước đầu nghiên cứu đa hình nucleotide đơn MC4R-rs17782313 ở trẻ 5-6 tuổi Hà Nội bằng phương pháp PCR-RFLP. Tạp chí Khoa học Đại học Quốc gia Hà Nội, chuyên san KHTN và Công nghệ. 31 (2015) 57-63. https://js.vnu.edu.vn/NST/article/view/84[22] L.T. Tuyết, T.Q. Bình, Associations of Single Nucleotide Polymorphism rs17782313 in Melanocortin 4 Receptor Gene with Anthropometric Indices in Normal and Obesity Primary School Children in Hanoi. NU Journal of Science: Medical and Pharmaceutical Sciences. 34 (2018) 1-7. https://doi.org/10.25073/2588 - https://doi.org/10.25073/2588-1132/vnumps.4107